2015
DOI: 10.15369/sujms.27.261
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-shift Magnetic Resonance Imaging Performed after Chemoembolization of Hepatocellular Carcinoma

Abstract: : We investigated whether the Lipiodol-derived signal accumulated in hepatocellular carcinoma HCC after transcatheter arterial chemoembolization TACE using Lipiodol oil-based contrast agent mixed with an anticancer agent, known as Lp-TACE, could be evaluated with chemical-shift magnetic resonance imaging MRI . The subjects were 25 HCC patients n 45 tumors who had undergone Lp-TACE and chemical-shift MRI of the abdominal region from April 1, 2000 to March 31, 2012. The regions of interest ROIs were set as large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Miyagami, et al reported that the range of the CT numbers in the Lipiodol region in HCC patients were 139 to 3062 HU. 11 From the result of the correlation of the CT numbers and the contrast medium concentration in Figure 5, 3000 HU was over 90 mg ml −1 concentration of the contrast medium using over 100 kV. Thus, the contrast medium extraction method is needed to be evaluate at 90 mg ml −1 concentration of the contrast medium.…”
Section: Discussionmentioning
confidence: 99%
“…Miyagami, et al reported that the range of the CT numbers in the Lipiodol region in HCC patients were 139 to 3062 HU. 11 From the result of the correlation of the CT numbers and the contrast medium concentration in Figure 5, 3000 HU was over 90 mg ml −1 concentration of the contrast medium using over 100 kV. Thus, the contrast medium extraction method is needed to be evaluate at 90 mg ml −1 concentration of the contrast medium.…”
Section: Discussionmentioning
confidence: 99%